Distribution and prevalence of scurf (Monilochaetes infuscans) on sweet potato (Ipomea batatas) in West Java, Indonesia - Sitaresmi Dewayani; Haris Maulana; Noladhi Wicaksana; Tarkus Suganda; Vergel Concibido; Agung Karuniawan (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Dewayani, Maulana H, Wicaksana N, Suganda T, Concibido V, Karuniawan A. 2021. Distribution and prevalence of scurf (Monilochaetes infuscans) on sweet potato (Ipomea batatas) in West Java, Indonesia. Biodiversitas 22: 2876-2883. Scurf (Monilochaetes infuscans) is a common sweet potato (Ipomoea batatas (L.) Lam.) tuber skin discoloration disease, that can cause significant yield loss, especially when tubers are destined for the export market. Despite the economic importance of the disease in West Java, Indonesia, there is a dearth of information on the distribution and severity of scurf disease. To address this gap, a disease survey was carried out across 28 fields in six districts (Bandung, Sumedang, Garut, Kuningan, Cianjur, and Bogor) of West Java from 2016 to 2018. Scurf disease prevalence was recorded by counting the number of infected tubers from 15 plant samples per field. Disease incidence was recorded when at least one infected tuber per plant was observed. Severity of scurf diseases was estimated by measuring the percentage of infected surface area, using AutoCAD map 2019. Results show that scurf was distributed across all locations surveyed. Disease incidence ranged from 1.68% (Cikadu) to 27.56% (Cilembu) while disease severity ranged from 7.92% (Cikadu) to 57.00% (Cilembu). Based on potato dextrose agar (PDA) culture plates, 68.57 % of tubers were infected with various fungi. Among them, M. infuscans (32.14 %) was the most prevalent and most widely distributed pathogen associated with the scurf disease across sweet potato fields in West Java, Indonesia. To effectively manage the disease and improve farmers’ income, it is imperative to establish effective and sound integrated disease mitigation strategies based on the results of this survey.